A honfoglalás kori íjak és íjászsírok problémakörének újabb megközelítése - Tihanyi Balázs (SZTE BTK Régészeti Tanszék Szeged, 2015)
The written sources and archaeological founds confirm that the bow was the main weapon of the Hungarian conquerors and in that period the horse-archers were the base of the army. Many scholars investigated the theme of the Hungarian bows already, but there are more questions than answers yet. The main problem is the nature of the finds: from this era we have mainly grave-finds and in the case of such functional type of equipments as weapons we cannot answer on scientific level the question of using of the bows. So my opinion is that - according to the needs of the 21st century - we must involve the methods of the natural sciences. So in this paper I try to investigate the problem of the graves equipped with archery equipments both archaeologically and anthropologically. The base of the anthropological investigations is the group of the entheseal changes. The activityrelated stress markers belong to this group: if a muscle (or a group of muscles) was loaded heavily and regularly it makes traces on the bone (hypertrophy at the attachment points of the involved muscles). Archery is a complex movement that involves a number of muscles from the shoulders to the fingers, so it is possible to separate from other labours. After the introduction of the anatomy of the archery and the international anthropological data, I give the interpretation of the 10th century cemetery of Sárrétudvari-Hízóföld (County Hajdú-Bihar) according to the archaeological and anthropological data. The scapulas, clavicles, humeruses, radiuses and ulnas of the 58 "archer" graves and 40 unarmed adult male graves were included to the macroscopic investigation. As a result I can say that the archaeological and anthropological data support each other, the individuals with archery equipment were well trained. There is high similarity in the groups of archery-muscles and the groups of registered hypertrophic attachment points in this series, so my opinion is that in ideal terms it is possible to decide if someone used the bow regularly, as a "life-style".
Keywords: Bölcsészettudományok; Történettudomány és régészet